The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Bio- And Chemo-Mechanical Processes in Geotechnical Engineering 2014
DOI: 10.1680/bcmpge.60531.014
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical processes and geotechnical applications: progress, opportunities and challenges

Abstract: Consideration of soil as a living ecosystem offers the potential for innovative and sustainable solutions to geotechnical problems. This is a new paradigm for many in geotechnical engineering. Realising the potential of this paradigm requires a multidisciplinary approach that embraces biology and geochemistry to develop techniques for beneficial ground modification. This paper assesses the progress, opportunities, and challenges in this emerging field. Biomediated geochemical processes, which consist of a geoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 100 publications
0
94
0
12
Order By: Relevance
“…The saturation C sink capacity may also change with the change in atmospheric concentration of CO 2 because it can enhance SOC turnover and potentially limit long‐term C sequestration in ecosystems depending on the plant community composition (Hofmockel, Zak, Moran, & Jastrow, ). An enhanced understanding of biochemical processes of SOC sequestration and of soil erosion control through pedo‐technical applications can create additional opportunities of C sequestration (Dejong et al., ). Pedo‐technical applications for SOC sequestration may include reverting agriculturally marginal lands to natural vegetation or replanting of a perennial vegetation (Post & Kwon, ), but the rate of SOC sequestration may be low and limited by other factors (e.g., availability of N, water).…”
Section: Processes and Factors Affecting Soil Organic Carbon Sequestrmentioning
confidence: 99%
“…The saturation C sink capacity may also change with the change in atmospheric concentration of CO 2 because it can enhance SOC turnover and potentially limit long‐term C sequestration in ecosystems depending on the plant community composition (Hofmockel, Zak, Moran, & Jastrow, ). An enhanced understanding of biochemical processes of SOC sequestration and of soil erosion control through pedo‐technical applications can create additional opportunities of C sequestration (Dejong et al., ). Pedo‐technical applications for SOC sequestration may include reverting agriculturally marginal lands to natural vegetation or replanting of a perennial vegetation (Post & Kwon, ), but the rate of SOC sequestration may be low and limited by other factors (e.g., availability of N, water).…”
Section: Processes and Factors Affecting Soil Organic Carbon Sequestrmentioning
confidence: 99%
“…supporting foundations and restoration of limestone buildings; DeJong et al . , ; Dhami, Reddy and Mukherjee ).…”
Section: Microbially Mediated Processes and Applicationsmentioning
confidence: 98%
“…Over the past 15 years, MICP has been tested for its potential as an innovative soil improvement technique for different purposes. While most of these tests were under laboratory conditions, the MICP technique has been proved to be suitable for use in applications such as strengthening loose sand, liquefaction control in saturated fine sand and fugitive dust control in desert areas (Dejong et al., ). A few field trials of these applications were also reported.…”
Section: Multi‐functionalitymentioning
confidence: 99%